2015
DOI: 10.1186/s12964-015-0085-y
|View full text |Cite
|
Sign up to set email alerts
|

The Rho GTPase RhoB regulates cadherin expression and epithelial cell-cell interaction

Abstract: BackgroundThe Rho GTPase RhoB has been proposed to be a tumor suppressor in cancer and is downregulated in various tumors including prostate. RhoB has different effects on cell migration depending on the cell type and conditions, but the molecular basis for this variability is unclear. RhoB regulates trafficking of membrane receptors and integrins. We have previously shown that RhoB depletion alters focal adhesion dynamics and reduces surface levels of β1 integrin in PC3 prostate cancer cells, correlating with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
6
18
0
Order By: Relevance
“…In parallel, E-cadherin, epithelial marker of EMT known to be downregulated notably by Slug, showed reduced levels of mRNA and protein. Similarly, it was reported very recently in prostate cancer cells 41 that RhoB silencing reduced E-cadherin expression only at the protein level, thus by a protein degradation rather than by a transcriptional regulatory mechanism. Interestingly, Slug expression is associated with poor survival in lung carcinoma, 42 similar to the loss of RhoB expression.…”
Section: Discussionsupporting
confidence: 69%
“…In parallel, E-cadherin, epithelial marker of EMT known to be downregulated notably by Slug, showed reduced levels of mRNA and protein. Similarly, it was reported very recently in prostate cancer cells 41 that RhoB silencing reduced E-cadherin expression only at the protein level, thus by a protein degradation rather than by a transcriptional regulatory mechanism. Interestingly, Slug expression is associated with poor survival in lung carcinoma, 42 similar to the loss of RhoB expression.…”
Section: Discussionsupporting
confidence: 69%
“…Rho signaling governs actin redistribution [32-41] and is implicated in various cellular responses including cell-cell adhesion and EMT [13, 22, 25, 42-45]. In the present work, we reported opposite effects of the KDM2B gene in the expression of RhoA/RhoB/RhoC- and Rac1-GTPases.…”
Section: Discussionsupporting
confidence: 56%
“…This observation implies a significant role of KDM2B in tumorigenesis and suggests the implication of actin cytoskeleton and small GTPases signaling in this phenomenon. Indeed, this assumption was postulated previously in various tumor cell models by analyzing the correlation of EMT with actin signaling and migration [13, 19-27]. Moreover, previous studies showed that the Serum glucocorticoid kinase 1 (Sgk1) plays a key role in EMT in colon carcinoma [28].…”
Section: Discussionmentioning
confidence: 84%
“…However, recent data have shown that RhoB expression is induced under conditions such as DNA damage, or treatment with growth factors or cytokines, suggesting that under particular circumstances, RhoB may favor towards human malignancy, including glioblastoma tumors [65,66]. In the present study, we show that when RhoB is silenced, both parental and their derivative-IE1 cells show a reduction in spread area compared to the RhoA or RhoC knockdown cells, an effect which has attributed to subsequent reduction of total surface levels of b1 integrin [67,68]. Moreover, in the presence of HCMV, an increased number of cellular projections was formed, a phenomenon which has also been observed in HCMV infected primary HFF cells, particularly at the late stages of lytic infection [49].…”
Section: Discussionsupporting
confidence: 53%